“Active Waiting”: Habits and the Practice of Conducting Qualitative Research - Matthew R. Hunt PhD (International Journal of Qualitative Methods, 2010)
Learning to conduct good qualitative research passes beyond the acquisition of research knowledge and technical skill. A variety of attributes and abilities are important in the research process such as creativity, flexibility, and inquisitiveness, among others. Quality in qualitative research also requires the development and practice of specific habits. Such habits are likely a taken-for-granted aspect of qualitative inquiry for seasoned researchers; they might not be as obvious for less experienced researchers or students. In this article the author examines the role of habits in and on the practice of qualitative research. To illustrate this topic, he examines how researcher habits can influence the pacing of an inquiry. Qualitative research requires the learned practice of active waiting: striking a balance throughout a research project between moving forward and advancing the research process and, on the other hand, allowing adequate time for the full development of each aspect of the research.